2021
DOI: 10.1007/s11071-021-07062-2
|View full text |Cite
|
Sign up to set email alerts
|

Single-coil metal detector based on spiking chaotic oscillator

Abstract: A remarkable feature of chaotic systems is high sensitivity, which makes them applicable to the construction of sensing devices. Various sensors can be developed based on chaotic oscillators, e.g., metal detectors, salinometers, inductive sensors, and optical sensors. Our study investigates the properties of the metal detector based on Sprott Case N chaotic oscillator equipped with a single inductive coil. A key feature of this circuit is the ability to operate in two modes: chaotic and spiking chaotic oscilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Figure 17 demonstrates the course of the experiments. Theaccuracy of target positioning at the automated test bench is approximately 50 µm, resulting in a relative error not more than 0.2% in linear displacement measurements [ 15 ]. Figure 18 presents the photograph of the used set of targets.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 17 demonstrates the course of the experiments. Theaccuracy of target positioning at the automated test bench is approximately 50 µm, resulting in a relative error not more than 0.2% in linear displacement measurements [ 15 ]. Figure 18 presents the photograph of the used set of targets.…”
Section: Resultsmentioning
confidence: 99%
“…In our experiments, we found that when using a stable generator of the harmonic waveform, the analog part of the metal detector also behaves stably, providing, after adjusting the sensitivity, the minimum number of false detections for a long time. At least, the stability of the circuit was found to be much higher than in the study of a metal detector based on the Sprott Case N system [ 15 ]. We believe that this is one of the reasons why the sensitivity of the Duffing oscillator-based detector is significantly higher.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations